Contrasting Effects of Long-Term Nitrogen Deposition on Plant Phosphorus in a Northern Boreal Forest - Palmqvist, Kristin; Nordin, Annika; Giesler, Reiner (Frontiers in Forests and Global Change, 2020)
Ecosystem responses to N deposition have a high variation across sites. Phosphorus (P), which can interact strongly with N, can be the cause to some of this. We quantified plant and O-horizon N and P concentrations and P stocks after 18 years in a long-term stand-scale (0.1 ha) N addition experiment (12.5 kg (N1) and 50 kg (N2) N ha-1 yr-1) in a c. 100 year old boreal Picea abies ((L.) Karst) forest. Basal area growth had increased by 65% in the N2 treatment compared to control, along with higher leaf area index, and lower litter decomposition. Higher tree growth occurred during c. 10 years thereafter resuming to control rates. We hypothesized that increased plant demand for P together with decreased recycling of organic matter in this N limited system may decrease plant available P, with consequences for longer-term biogeochemistry and production. However, resin extractable P did not differ between the three treatments (0.32 kg P ha-1), and plant NP ratios, P concentrations, and O-horizon P characteristics were similar in the N1 and control treatments. The N2 treatment doubled total P in the O-horizon (100 vs. 54 kg P ha-1), explained by an increase in organic P. The N concentration, NP ratio, and spruce needle biomass were higher in N2, while the P stock in current year needles was similar as in the control due to a lower P concentration. In addition to P dilution, increased light competition and/or premature aging may have caused the reduction of N stimulated growth of the trees. For the dominant understory shrub (Vaccinium myrtillus (L.)) no changes in growth was apparent in N2 despite a significantly higher NP ratio compared to control (15 vs. 9, respectively). We therefore conclude that increased NP ratio of vegetation can not be used as a sole indicator of P limitation. The vegetation and O-horizon changes in N2 were still large enough to merit further studies addressing whether such high N loads may alter ecosystem biogeochemistry towards P limitation. For the lower N addition rate, relevant from an anthropogenic N deposition perspective, we suggest it had no such effect.